2012
DOI: 10.1590/s1679-45082012000400014
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of three classifications of proximal humeral fractures

Abstract: Objective: To propose a new system for classifying proximal humeral neck fractures, and to evaluate intra-and interobserver agreement using the Neer system that is the most commonly used in the area and the Arbeit Gemeinschaft für Osteosynthesefragen system created by an European group, and a new classification system proposed by the authors of this study. Methods: A total of 56 patients with proximal humeral fractures were selected, and submitted to digitized simple radiography in antero-posterior shoulder an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…However, computed tomography is expected to facilitate and improve the reproducibility of the analyzed fractures, providing a greater intra-observer agreement, enabling a better choice of treatment and a more reliable and reproducible classification system. 7,10 Despite numerous complaints regarding its reproducibility, Neer classification is widely accepted and commonly used to guide treatment and anticipate prognosis; it is pedagogically useful, of easy learning and separates fractures into broad categories, being easy to understand. 5,7 AO classification (Arbeitsgemeinschaft für Osteosynthesefragen) divides fractures according to their complexity and facilitates choice of treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, computed tomography is expected to facilitate and improve the reproducibility of the analyzed fractures, providing a greater intra-observer agreement, enabling a better choice of treatment and a more reliable and reproducible classification system. 7,10 Despite numerous complaints regarding its reproducibility, Neer classification is widely accepted and commonly used to guide treatment and anticipate prognosis; it is pedagogically useful, of easy learning and separates fractures into broad categories, being easy to understand. 5,7 AO classification (Arbeitsgemeinschaft für Osteosynthesefragen) divides fractures according to their complexity and facilitates choice of treatment and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…7,10 Despite numerous complaints regarding its reproducibility, Neer classification is widely accepted and commonly used to guide treatment and anticipate prognosis; it is pedagogically useful, of easy learning and separates fractures into broad categories, being easy to understand. 5,7 AO classification (Arbeitsgemeinschaft für Osteosynthesefragen) divides fractures according to their complexity and facilitates choice of treatment and prognosis. The AO is one of the most complete classification system, however, its intra-and inter-observer reproducibility has reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other PHF classification systems, the Neer system has shown limited interobserver and intraobserver agreement. 7,8,11,28 A recent systematic literature review found that levels of interobserver and intraobserver agreement for PHF classification was lowest for x-ray, increased with two-dimensional (2D) computed tomography (CT), and highest with 3D CT. The same study suggested CT may increase interobserver agreement to a greater extent for less experienced observers.…”
mentioning
confidence: 99%